Synthesis, in vitro antiproliferative activity, and in silico studies of fused tricyclic coumarin sulfonate derivatives - El-Gamal, Mohammed I.; Oh, Chang-Hyun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2014)
A series of fused tricyclic coumarin sulfonate derivatives was synthesized. Their in vitro antiproliferative activities against a panel of 57 human cancer cell lines of nine different cancer types were tested at the NCI. Compounds 1e, 1f, 1h, 1i, and 1o showed the highest mean percentage of inhibition values over the 57 cell line panel at 10 mu M, and they were further tested in 5-dose testing mode to determine their IC50 values. Compounds 1e, 1f, and 1o were more selective against leukemia and colon cancer subpanels, while compounds 1h and 1i showed broad-spectrum anticancer activities. Compounds 1e, 1f, 1h, 1i, and 1o demonstrated high selectivity towards cancer cell lines than RAW 264.7 macrophages. Compound 1h exerted lethal effect over NCI-H522 NSCLC, SK-MEL-5 melanoma, and A498 renal cancer cell lines with percentage of inhibition values of 114.10%, 103.23%, and 100.52% at 10 mu M concentration, respectively. Moreover, the IC50 value of compound 1o against HT29 colon cancer cell line was 532 nM. Compounds 1e, 1f, 1h, 1i, and 1o were tested for inhibitory effect over cyclooxygenase-2 (COX-2) enzyme as a possible mechanism of action. Furthermore, in silica studies were conducted to check the compliance of those five compounds with Lipinski's rule of five, and hence estimate their oral bioavailability. (c) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: HUMAN-MALIGNANT-MELANOMA; RAW 264.7 MACROPHAGES; NF-KAPPA-B; CYCLOOXYGENASE-2 EXPRESSION; BIOLOGICAL EVALUATION; ANTICANCER ACTIVITIES; STEROID SULFATASE; BREAST-CANCER; UP-REGULATION; CELL-LINES